Ile było wersji poezji Karola Wojtyły w przekładzie Jerzego Pietrkiewicza? Wstępne rozpoznanie tematu - Moczkodan, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article discusses problems involved in the translation of Karol Wojtyła’s poetry into English, including the circumstances of obtaining by the translator (Jerzy Pietrkiewicz) legal rights to the texts, deciding the translational techniques applied in the process of interlinguistic transfer, as well as other difficulties reported by the translator during his work on the first volume of English poetry by John Paul II.
How Many Versions of Karol Wojtyła’s Poetry Were Translated by Jerzy Pietrkiewicz? Initial Recognition of the Topic
Keywords: Jerzy Peterkiewicz; Karol Wojtyla; John Paul II; poetry; translation; Jan Paweł II; poezja; tłumaczenie